A comparative investment analysis: Is it better to invest in venture capital or in the motion picture industry? - Lasaygues, Victor José (2017)
This paper analyses and compares the profitability and risks of the movie industry against venture capital investment. For the movie industry, by studying the data of 524 movies made by 13 studios from 2011 to 2014. For venture capital investments by collecting insight on the profitability of venture capital investment from seven academicals articles. The study suggests that both industry exhibit similar pattern in term of dispersion, but that movie industry is more profitable than venture capital investment. At the same time the higher profit of the movie industry result also in higher risks for the investors, making this industry only desirable for investors looking for an aggressive investment strategy.